2005
DOI: 10.1115/1.1992525
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Structural and Mechanical Anisotropy in Fibroblast Populated Collagen Gels

Abstract: An in vitro model system was developed to study structure-function relationships and the development of structural and mechanical anisotropy in collagenous tissues. Fibroblast-populated collagen gels were constrained either biaxially or uniaxially. Gel remodeling, biaxial mechanical properties, and collagen orientation were determined after 72 h of culture. Collagen gels contracted spontaneously in the unconstrained direction, uniaxial mechanical constraints produced structural anisotropy, and this structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 38 publications
5
115
0
Order By: Relevance
“…Associated with the tension-dependent stress-fiber assembly is the development of structural anisotropy. For example, uniaxially constrained, fibroblast-populated collagen gels develop a high degree of fiber alignment and mechanical anisotropy, while gels constrained biaxially remain isotropic (Thomopoulos et al 2005). (ii) Cells "sense" the stiffness of their substrates and exert smaller tractions on more compliant substrates (Discher et al 2005).…”
Section: Review Of the Key Biochemical Processes And Experimental Obsmentioning
confidence: 99%
“…Associated with the tension-dependent stress-fiber assembly is the development of structural anisotropy. For example, uniaxially constrained, fibroblast-populated collagen gels develop a high degree of fiber alignment and mechanical anisotropy, while gels constrained biaxially remain isotropic (Thomopoulos et al 2005). (ii) Cells "sense" the stiffness of their substrates and exert smaller tractions on more compliant substrates (Discher et al 2005).…”
Section: Review Of the Key Biochemical Processes And Experimental Obsmentioning
confidence: 99%
“…Cross-bridge cycling between the myosin motor proteins and actin filaments generates active contractility in the actin cytoskeleton. Several experimental studies have demonstrated that a reduction in cell tension leads to the dissociation of stress fibres (Franke et al, 1984;Kolega, 1986;Burridge and Chrzanowska-Wodnicka, 1996;Tan et al, 2003;Thomopoulos et al, 2005).…”
Section: Constitutive Formulation For the Active Behaviour Of The Celmentioning
confidence: 99%
“…Images of the tissue constructs (1024 X 768 pixels) were transferred to a personal computer, and the titanium oxide marker centroids were detected semi-automatically by threshholding the binary image (Scion Image, Frederick, MD). As described elsewhere 32 , homogeneous, two-dimensional finite Lagrangian strains (i.e., normal strains E xx and E yy , and shear strain E xy ) were computed from the digitized marker coordinates at each time point after t* referenced to the pre-switch configuration immediately prior to t*. In the steady state, the final deformation relative to the pre-switch reference configuration (i.e.…”
Section: Estimating the Passive Response To Altered Loading Conditionsmentioning
confidence: 99%
“…Therefore, deformation of the tissue was monitored throughout the loading experiment for a representative case of t* = 24 hours (n = 4). Before culture media was added to float the gel, a 3 × 3 array of nine titanium oxide markers was carefully painted with a fine sterile brush tip on the central third of the exposed tissue surface, where the strain field has been shown to be relatively homogeneous 32 . Throughout the course of the experiment, the construct and dish were intermittently moved to a photography copy stand for imaging with a digital camera (PowerShot G2, Canon Inc.).…”
Section: Estimating the Passive Response To Altered Loading Conditionsmentioning
confidence: 99%